Between- and within-country distributional impacts from harmonizing carbon prices in the EU - Landis, Florian; Fredriksson, Gustav; Rausch, Sebastian (Working papers of the Center of Economic Research at ETH Zurich, 2021)
This paper examines the distributional impacts from (i) harmonizing prices for carbon dioxide emissions across sectors and EU countries and (ii) using alternative rules for carbon revenue distribution. We develop a numerical multi-country multi-sector general equilibrium model of the EU-27 economy which resolves household income deciles, based on micro-survey data on expenditure and income, and markets for fossil fuels, electricity, and (EU-wide and national) tradeable emissions rights. We find that carbon price harmonization yields efficiency gains at the EU level. The distributional effects between countries vary and depend largely on the redistribution of carbon revenues. Based on the rules currently in place in Phase IV of the EU ETS, efficiency gains flow disproportionately to low-income countries. Within-country incidence is progressive or neutral for most countries when revenue redistribution is ignored, and is not much affected by carbon price harmonization. Per-capita-based revenue redistribution rules lead to strong progressive outcomes and yield gains for low-income households. Evaluating different policy options using a social welfare function that incorporates inequality aversion suggests that there is no trade-off between efficiency and equity in harmonizing carbon prices in the EU economy.
Keywords: Graue Literatur